Total anthocyanine content and antioxidant density of some Hungarian sour cherry varieties - Veres, Zs.; Holb, I. J.; Nyéki, J.; Szabó, Z.; Fári, M. G. (International Journal of Horticultural Science, 2005)
Evidence suggests that a diet high in fruits and vegetables may decrease the risk of chronic diseases, such as cardiovascular disease and cancer, and phytochemicals including phenolics, flavonoids and carotenoids from fruits and vegetables may play a key role in reducing chronic disease risk. Recent research has proven that sour cherry (Prunus cerasus L.) is a valuable natural source of some bioactive compounds important in human health preservation. In our work, we identified the total antioxidant activity, anthocyanine content and "antioxidant density" of sour cherry varieties named "Újfehértói fürtös", "Debreceni bőtermő", "Kántorjánosi" and "Érdi bőtermő" and those of the "Bosnyák" sour cherry clones. "Antioxidant density" is a biological value indicator obtained in a synthetic way, which indicates the antioxidant capacity of the particular food, e. g. fruit and vegetable, related to 1 Calorie.